1979
DOI: 10.1577/1548-8659(1979)108<473:eosrot>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Solar Radiation on the Dynamics of Dissolved Oxygen in Channel Catfish Ponds

Abstract: The daytime increase in dissolved oxygen (DO) concentration of pond waters may be estimated from solar radiation, chlorophyll a concentration, and percentage O2 saturation at dawn (coefficient of multiple determination, R2 = 0.83), or from solar radiation, Secchi disk visibility, and percentage O2 saturation at dawn (R2 = 0.80). A computer simulation model for predicting the effects of cloudy weather (low solar radiation) on DO depletion was developed for channel catfish ponds. The model incorporates the equat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 0 publications
0
25
0
1
Order By: Relevance
“…In our study, DO in the surface water was closely related to the respiration of plankton algae. Cloudy weather profoundly influenced DO concentrations in ponds (Romaire and Boyd, 1979). On clear days, there is sufficient light for high rates of photosynthesis, and DO concentrations normally are high.…”
Section: Gas Transfer Velocites Of Ch 4 and Comentioning
confidence: 99%
“…In our study, DO in the surface water was closely related to the respiration of plankton algae. Cloudy weather profoundly influenced DO concentrations in ponds (Romaire and Boyd, 1979). On clear days, there is sufficient light for high rates of photosynthesis, and DO concentrations normally are high.…”
Section: Gas Transfer Velocites Of Ch 4 and Comentioning
confidence: 99%
“…According to the empirical model presented by Romaire & Boyd (1979), had this Secchi depth been attained in a pond of 1 m depth, diel minimum DO should readily have fallen below 622. pm01 l-l (2.0 mg I-'), and should have reached zero during the 2 periods of low irradiance, yet neither of these conditions was realized. Die1 minima (1) never reached zero; (2) were below 31.2 pm01 1-' (1.0 mg 1-l) on only 2 of 14 dates (including the second day of low light but not the first); (3) were otherwise always greater than 62.5 pm01 I-' (2.0 mg I-'); and (4) exceeded 100 pm01 1-' on the dates following the lowest excursions.…”
Section: Stabilitymentioning
confidence: 99%
“…The crash phenomenon has been described repeatedly, but wlthout consistent interpretation (Abeliovich 1967, Barica 1975, Seymour 1980, Motzkin et al 1982, Boyd 1990, Erez et al 1990). Modeling and experimentation specific to pond communities have elucidated factors in production (Murphy 1962, Romaire & Boyd 1979, Laws & Malecha 1981, Grobbelaar 1989, but have less frequently addressed the question of stability directly (Krom et al 1989, Piedrahita 1990, 1991, Szyper et al 1991.…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes atypical seasonal conditions can largely alter the primary productivity of phytoplankton. For example, cloudy days cause a substantial decrease in photosynthetic activity of phytoplankton (Romaire & Boyd 1979;Kwang-Seuk et al 2003). Behrenfeld et al (2002) observed a clear relation between primary production and photoacclimation in oceanic algae.…”
Section: Introductionmentioning
confidence: 99%